CMM recovery, utilization and cogeneration by compressor plants - Bulat, A.F.; Kirik, G.V.; Zharkov, P.E.; Bluss, B.O.; Shevchenko, V. (Геотехнічна механіка, 2016)
The article presents the designed schemes and compressor plants for degassing coal beds and utilizing coal mine methane (CMM) and automatic system for controlling their operation. Interdependence between methane-bearing coal structure, permeability and absorption properties are analyzed. A model of influence of gases, which differ by their sorption energy, on the coal bed and possible schemes for intensifying methane recovery from the coal beds are described. A plant was designed for degassing the underground beds, in which rotary compressor pumps out the gas mixtures and degases the beds without characteristic formation of crystalline hydrate with methane. A station was designed for mine gas utilization. A method is proposed for methane recovery, which assumes pumping of carbon dioxide into the coal bed, which, due to the higher sorption capacity than that of methane, displaces methane adsorbed by the coal. Plants УКГ (Compressor GasUtilizing Plant – CGUP) were designed for methane utilization and combustion in special chamber and for preventing methane from escaping into atmosphere, or for feeding it to the equipment for use in energy sector (production of electricity and heat). The experience on using this technology and equipment with the view to increase the coalbed methane (CBM) recovery from the coal beds is presented.